UPAYA MENJAGA KESINAMBUNGAN PERIKANAN TUNA MADIDIHANG DI DESA TULEHU, KABUPATEN MALUKU TENGAH - Hehanussa, Kedswin G; Tuhumury, Julian; Hutubessy, B G; Pailin, J B (Balobe: Jurnal Pengabdian Masyarakat, 2022)
Yellowfin tuna is the leading prima donna in the capture fisheries sector in Maluku Province with a total national contribution of the two foreign exchange earners. The increase in production volume has not been able to meet the increasing demand for regional and global markets. This has led to an increase in fishing intensity in almost all Indonesian waters. Especially in Maluku. The increasing intensity of fishing causes yellowfin tuna to experience fishing pressure which can result in a decrease in stock size, both individual size and population size. The method used is the delivery of theoretical material and interactive discussions to fishermen. The results of the counseling on efforts to maintain the sustainability of the yellowfin tuna fisheries show that the community understands the importance of the availability of catch data both in the number and size of fish caught. The community must also participate in efforts to limit the number of fish caught because it is a wise thing to provide opportunities for fish to reproduce. This counseling is a very relevant suggestion to the condition of the available yellowfin tuna fishery resources